What can Aotearoa New Zealand learn from the Australian Sunsmart Story? A qualitative study - Bronwen M. McNoe; Ryan Gage; Louise Signal (Elsevier, 2022)
Abstract Objective: To explore the views of stakeholders in Australia concerning skin cancer primary prevention and identify successful strategies used that may be translatable to other jurisdictions. Methods: In‐depth stakeholder interviews with experts engaged in skin cancer prevention advocacy and action in Australia. Results: A number of important facilitators were identified including: the use of good scientific evidence (including economic), strong leadership, legislation and strategic documents, engaging the media particularly with the use of personal stories and garnering public support. A number of barriers were also identified including: a lack of funding (particularly nationally), variation by state, apathy and the long latency of skin cancer. Conclusions: Advocates identified a number of key strategies that were used to gain momentum in achieving Australia's comprehensive Sunsmart program. These included: strong leadership, legislation including that banning solaria and workplace health and safety legislation, a critical mass of key advocates from a range of disciplines including clinicians and patients, and the advantageous use of media to drive change. Implications for public health: Australia demonstrates what can be achieved when skin cancer prevention is taken seriously. The challenge for other nations is to apply the lessons learnt in Australia to our own jurisdictions.